Effect of a dietary combined vitamin C and E supplementation on the liver, kidneys and brain arginase activity in non-pregnant and pregnant rats with streptozotocin-induced diabetes - Erisir, M.; Naziroglu, M.; Tasdemir, B.; Simsek, M. (Ecole Nationale Veterinaire Toulouse, 2006)
As nitrogen metabolism is exacerbated during diabetes mellitus or/and pregnancy, and because arginase catalyses the arginine hydrolysis into ornithine and urea, this enzyme activity as well as the ornithine content were investigated in tissues (liver, kidney and brain) from pregnant or non pregnant streptozotocin (STZ) diabetic rats, dietary supplemented or not with antioxidant vitamins (C and E). Sixty 12 week old female Wistar rats were randomly divided into 6 equal groups according to their gestational status and the dietary treatments. The groups 1 (non pregnant) and 2 (pregnant) received only intraperitoneal injection of citrate buffer and served as controls, whereas the animals of the groups 3 (non pregnant) and 4 (pregnant) were treated with STZ (40 mg/kg) and those of the groups 5 (non pregnant) and 6 (pregnant) were submitted to STZ administration and to a dietary combined ascorbate and -tocopherol acetate (1 g and 600 mg/kg food respectively) supplementation for 20 days. Except for the kidneys from not supplemented diabetic rats in which the arginase activity and the ornithine content were significantly increased in pregnant rats, no significant difference was evidenced between pregnant and non pregnant females. The arginase activity and the ornithine content were dramatically enhanced in the liver of diabetic animals (pregnant or not) (p<0.001), whereas these 2 parameters were reduced in kidney and in brain, particularly in the non pregnant females. By contrast, in supplemented animals, tissue enzyme activities and ornithine quantities were similar to those observed in healthy rats. showing that vitamin C and E oral treatment significantly attenuate nitrogen perturbations linked to diabetes. These results suggest that the oxidative stress would participate to the development of metabolic disorders and organ dysfunctions observed in diabetes mellitus.
Keywords: diabetes; arginase; ornithine; vitamin C and E combination; pregnancy